When are we going to change the learning curve lecture? - Hurley, W.J. (Computers & operations research, 1996)
Most introductory textbooks in engineering economics, production management, and accounting develop the idea of a learning curve, focusing on the standard power model: y(x) = alpha x to the -beta power. However, a well-known problem with this functional form is that, as output, x, gets large, y(x) goes to zero. So if y measures labor hours, and the production run is large, the power model implies that the labor hours per unit will fall to zero, and for most types of production technologies subject to a learning effect, this is just not the case. Yet this technology remains the centerpiece of pedagogical efforts. It is shown that, in a forecasting context, use of the power function can lead to significant forecast error. Moreover, it is also argued that other, more realistic variations of the standard power curve, such as the De Jong model, are easy to estimate using the nonlinear optimization features available with most spreadsheets.